PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS V SDN 021 SITORAJO KIRI - Damhuri Damhuri (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is a classroom action research that aims to improve the learning outcomes of students PKN classV of SD Negeri 021 Sitorajo Kiri through Problem Based Learning Model. The subjects of the study werestudents of class V of SD Negeri 021 Sitorajo Kiri which amounted to 21 people. This study aims to determinethe improvement of PKN student learning outcomes in improving the quality of learning PKN that is with theapplication of problem based learning model. This study presents the results of student learning tests, showing asignificant improvement with teaching applying problem based learning model. Technical analysis of data thatresearchers use to measure learning outcomes trought results end of cycle I which the average value numbered75.53, then greet the cycle II 83.16. So the increase from cycle I to cycle II is 7.47. In addition, the observationsheet was also conducted to observe the activities of teachers and students during the lesson, by filling in theblanksheet columns that have been provided that are used for data collection about the activities of teachers andstudents learning class V of SD Negeri 021 Sitorajo Kiri. The average activity of student learning duringlearning in cycle I is 65 and in cycle II is 95 and ability of teacher in cycle I average 60 and in cycle II averageincrease to 95. From research above, it can be concluded that application of learning model based on problemscan increase student learning results PKN class V of SD Negeri 021 Sitorajo Kiri.